Analysis of the Internet Marketing Strategy of Electronic Games — Taking Hongkai: Star Rail as an Example - Li, Yichen (Transactions on Economics, Business and Management Research, 2024)
With the popularization and rapid development of the Internet, the electronic game market has shown a booming trend worldwide. At the same time, online marketing has become a marketing tool that cannot be ignored. As a new game released in 2023, Hongkai: Star Rail has gained a wide market in the world with its excellent game quality based on the flexible use of online marketing. Taking Hongkai: Star Rail as an example, this paper deeply explores the current situation of online marketing in the electronic game industry. This paper describes three representative online marketing strategies in detail and analyzes their respective advantages and disadvantages. Finally, some specific opinions are put forward for the shortcomings of the above strategies. In summary, this paper comprehensively analyzes the current situation and optimization direction of online marketing of electronic games, and provides valuable reference and inspiration for researchers and practitioners in related fields.